I'll be seeing you [large type] : a memoir - Berg, Elizabeth (Random House Large Print, 2020)
"For as long as Elizabeth can remember, she has watched her father trail after her mother, kissing her multiple times a day and holding her hand. She watched her mother smooth the lines in her father's face and pay attention to his every move, even when she was desperate for some time to herself. When her parents began to age, Elizabeth and her siblings are placed in the difficult position of taking over more and more supportive roles and tasks. They fix their parents' home, negotiate finances, eventually weather the back and forth of will they or won't they move into a nursing facility; finally they do. Berg gracefully takes readers through navigating the emotional and physical challenger of guiding parents through the final stages of life. In this touching and heart-warming memoir, Berg includes raw accounts of disagreements, encouraging stubborn parents, and dealing with her own heartache and loss. Berg confront both the realities of the situation and the brighter, happy, funny and endearing moments and memories"--